Analisis Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Soal Pecahan melalui Pembelajaran PBL untuk Siswa Kelas VII SMPK St. Paulus Karuni - Deta, Dominggus Umbu; Lede, Yulius Keremata; Making, Samuel Rex M (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to determine students’critical thinking abilities in solving problems on fractions after PBL learning for class VII students at SMPK St. Paulus Karuni. This study used descriptive qualitative method. The research subjects were 3 students from 32 class VII C students at SMPK St. Paulus Karuni who took the test. The three subjects were selected based on the categories obtained, namely high, medium, and low categories. Data was obtained from the results of studens’ tests completing questions on fraction and interviews with three subjects. Based on the research results of subjects with high critical thinking own four indicators, namely interptretation, analysis, evaluation, and inrefence abilties. At the interpretation stage the subject is able to understand the questions shown, at the analysis stage the subject is able create a mathematical model of the problem, at the evaluation stage the subject is able to use the right strategy based on the mathematical model created at the analysis stage and at the inference stage the subject is able to conclude the answer correctly. The critical thinking subject is going own critical thinking indicators. In problem one the subject was able to fulfill the four indicators of critical thinking. In problem two and the three subject was unable to fulfill the critical indicatoirs, namely at the analysis stage he was unable to create a mathematical model and at the inference the stage subject was unable to make appropriate conclusions. The subject had low critical thinking own four indicators.